Dissolved Organic Matter Cycling in the Coastal Upwelling System Off Central Peru During an “El Niño” Year - Igarza, Maricarmen; Dittmar, Thorsten; Graco, Michelle; Niggemann, Jutta (Frontiers in Marine Science, 2019)
The Peruvian upwelling system (PUS) is among the most productive regions in the ocean, with high rates of primary production and an intense oxygen minimum zone (OMZ). The main perturbation of this system is associated to “El Niño” (EN), which affects water mass distribution and reduces primary production. Previous studies in the PUS provided first insights into the dynamics of dissolved organic matter (DOM), but high-resolution studies involving the molecular characterization of the DOM pool to reveal the processes that affect the carbon cycle in this highly productive system are lacking. We characterized the molecular composition of solid-phase extractable DOM (SPE-DOM) in the coastal upwelling system off Central Peru and linked it to specific processes that affect DOM cycling. Seasonal sampling (April, August and December) was carried out off Central Peru (12°S) during 2015, a low productivity year marked by EN conditions. The DOM molecular composition was obtained via Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR-MS). Solid-phase extractable dissolved organic carbon (SPE-DOC) concentrations showed significant differences (p<0.05) between the water masses present off central Peru. In order to explore if changes in SPE-DOC concentrations were the result of water mass mixing, we applied a conservative mixing model. The model revealed a non-conservative behaviour of SPE-DOC and allowed us to identify two distinct groups of samples with increased and decreased SPE-DOC concentrations respectively, and one group of samples inside the conservative mixing range. Differences in environmental parameters characterizing these groups were in accordance with respective processes associated to production and degradation of SPE-DOC. The trends observed for molecular parameters revealed the imprint of processes related to DOM production and DOM degradation, both biotic (microbial degradation) and abiotic (photodegradation). Our study suggests that even under low productivity conditions like EN, there is an active cycling of the DOM pool off central Peru.